2018
DOI: 10.1038/s12276-018-0186-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of type 1 diabetes mellitus and subsequent osteoblastic β-catenin activation on trabecular and cortical bone in a mouse model

Abstract: Type 1 diabetes mellitus (T1DM) is a pathological condition associated with osteopenia. WNT/β-catenin signaling is implicated in this process. Trabecular and cortical bone respond differently to WNT/β-catenin signaling in healthy mice. We investigated whether this signaling has different effects on trabecular and cortical bone in T1DM. We first established a streptozotocin-induced T1DM mouse model and then constitutively activated β-catenin in osteoblasts in the setting of T1DM (T1-CA). The extent of bone loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…In contrast to glucose metabolism, deletion of osteogenic Dkk1 partially prevented T1DM-induced trabecular bone loss and completely prevented cortical bone loss. T1DM is known to reduce bone quantity and furthermore suppress the Wnt/β-catenin pathway 18,19,28,31,32 . Our results are consistent with another study postulating differential effects of β-catenin overexpression in mice with T1DM on trabecular and cortical bone 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to glucose metabolism, deletion of osteogenic Dkk1 partially prevented T1DM-induced trabecular bone loss and completely prevented cortical bone loss. T1DM is known to reduce bone quantity and furthermore suppress the Wnt/β-catenin pathway 18,19,28,31,32 . Our results are consistent with another study postulating differential effects of β-catenin overexpression in mice with T1DM on trabecular and cortical bone 31 .…”
Section: Discussionmentioning
confidence: 99%
“…T1DM is known to reduce bone quantity and furthermore suppress the Wnt/β-catenin pathway 18,19,28,31,32 . Our results are consistent with another study postulating differential effects of β-catenin overexpression in mice with T1DM on trabecular and cortical bone 31 . Similar to our study, Wnt activation only ameliorated cortical, but not trabecular bone loss induced by T1DM, an effect the authors proposed to be dependent on differential Wnt16 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown the dysregulation of β-catenin signaling in many tissues in diabetes, including in osteoblasts ( Yee et al, 2016 ; Chiang et al, 2012 ; Welters and Kulkarni, 2008 ; Jin, 2008 ). Reduced WNT/β-catenin signaling leads to impaired osteoblast activity in several mouse models of diabetes, including the streptozotocin (STZ)-induced T1DM mouse model used in our previous work ( Daley et al, 2019 ; Chen et al, 2018 ; Yee et al, 2016 ). Previous studies have shown that diabetic bone abnormalities resulting from T1DM more severely affect the trabecular rather than the cortical bone ( Daley et al, 2019 ; Shah et al, 2018 ; Jiang and Xia, 2018 ), and trabecular bone is known to be more readily affected by changes in β-catenin ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The canonical WNT pathway activates β-catenin signaling in osteoblasts and osteoblast precursor cells, and is essential for osteoblast differentiation and proliferation ( Monroe et al, 2012 ). Several recent studies have shown that WNT/β-catenin signaling is impaired in osteoblasts in T1DM rodent models, resulting in decreased osteoblast activity ( Chen et al, 2018 ; Yee et al, 2016 ). β-catenin promotes the transcription of target genes by complexing with TCF/LEF transcription factors ( Liu and Habener, 2008 ), and our laboratory has previously reported that there are functional TCF/LEF cis-elements in the lysyl oxidase promoter ( Khosravi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Distinct from the amount of remodeled bone is the rate of trabecular or cortical bone turnover, often measured as the bone formation rate per unit of bone volume (BFR/BV) 146 . In humans, the BRF/BV is a well established measure 147,148 that is affected by age, 149 use, 42,150 and comorbidities 39,151,152 . In animal models, it is used to assess both the rate of bone remodeling and bone healing 153 .…”
Section: Bone Formation During Normal Homeostasismentioning
confidence: 99%